Stakeholding as a new development strategy for Saudi Arabia - Giacomo Corneo (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
The transition from an oil-based to a knowledge-based economy requires that the Saudi population dramatically increases its level of human capital. This paper argues that noncognitive skills may be a bottleneck in the formation of human capital and proposes a policy to indirectly strengthen those skills. The core of the proposal is a government-financed gift to each Saudi citizen reaching adult age, the SSGY.
Keywords: O0; Z1; 330; Saudi Arabia; Stakeholder Society; Value Systems; Economic Development; Entwicklungsstrategie; Informationsgesellschaft; Bildungsinvestition; Subvention; Stakeholder; Saudi-Arabien